2020
DOI: 10.1002/jcla.23648
|View full text |Cite
|
Sign up to set email alerts
|

Differentially expressed microRNAs in peripheral blood mononuclear cells of non‐segmental vitiligo and their clinical significance

Abstract: Background Vitiligo is a frequent acquired depigmentation skin disease due to a loss of melanocytes. This study sought to characterize the expression pattern of microRNA (miRNA) in the peripheral blood mononuclear cells (PBMCs) of non‐segmental vitiligo (NSV) patients. We also screened for molecular markers that can be used to evaluate the clinical stages of NSV. Methods The miRNA expression profile in the PBMCs of four patients with progressive NSV and four healthy controls was determined using high‐throughpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…31 Many miRNAs are dysregulated in nonsegmental vitiligo 32,33 and have been shown to target major pigmentation genes like Tyr and MITF. 34 It has been shown that divergently expressed miRNAs contribute to the pathogenesis of nonsegmental vitiligo 35 ; for example, miRNA-145 has been shown to have a key role in regulating melanogenesis as suggested by a number of studies. 22,36 As far as we know, miRNA-377 expression hasn't been estimated in vitiligo before.…”
Section: Discussionmentioning
confidence: 99%
“…31 Many miRNAs are dysregulated in nonsegmental vitiligo 32,33 and have been shown to target major pigmentation genes like Tyr and MITF. 34 It has been shown that divergently expressed miRNAs contribute to the pathogenesis of nonsegmental vitiligo 35 ; for example, miRNA-145 has been shown to have a key role in regulating melanogenesis as suggested by a number of studies. 22,36 As far as we know, miRNA-377 expression hasn't been estimated in vitiligo before.…”
Section: Discussionmentioning
confidence: 99%
“…We explored the correlation between the expression of miRNAs and the area of lesions by Spearman correlation coefficient using IBM ® SPSS Statistics Software (V27.0). 23 …”
Section: Methodsmentioning
confidence: 99%
“…Another study also analyzed miRNA expression profile in the PBMCs of NSV patients (Zhang et al, 2020). The top 10 upregulated miRNAs included miR- 335-5p, miR-20a-5p, miR-514a-3p, miR-144-5p, miR-450b-5p, miR-369-3p, miR-101-3p, miR-142-5p, miR-19b-3p, and miR-340-5p.…”
Section: Altered Mirna Expression In Peripheral Blood Mononuclear Cellsmentioning
confidence: 99%